The Effectiveness of Fermi Problem-Based Learning on Improving Communication Skills among United Arab Emirates Cycle Two Students - Bani-Hamad, Adwan Mohammad Hasan; Al-Kalbani, Mouza Saif Ali (Archives of Business Research, 2023)
Communication skills are necessary for students to empower them in facing new global challenges. Thus, this study employed Fermi Problem-based Learning to improve communication skills in teaching Science among the Cycle Two students in United Arab Emirates. It also examined the effectiveness of this strategy between grade 7 and grade 8 students. This study used quasi-experiment design. The instrument for research was pre and post-test using Communication Skills which was prepared by the researcher. The participants purposively selected according to a certain criterion, then divided for the experimental group, consisting of 15 grade seven and eight students, from Ramah Primary and Secondary School, they were taught Science units using the Fermi Problem-Solving method for 6-weeks, Whereas the control group consisted of 15 grade seven and eight students who were taught the same science units using traditional methods. The data were analysed using the Two Way ANCOVA to determine the effectiveness of the strategy on improving their communication skills and to determine the variation in the effectiveness of the strategy between grade 7 and grade 8 students. The findings revealed the effectiveness of the Fermi problem based learning strategy in developing the communication skills in teaching Science among the United Arab Emirates Cycle Two students. The findings also demonstrated that there were no significant differences in the effectiveness of the strategy amongst grade 7 and grade 8 students. Thus, Fermi Problem-Based learning is considered an effective strategy in teaching Science and in improving students’ communication skills and suitable for all Cycle Two students. In addition, this strategy can help teachers to integrate Fermi Problem-Solving into their teaching practice in order to achieve the objective of teaching science in the 21st century.